2006
DOI: 10.1086/499410
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Hypophosphatemic Rickets with Hypercalciuria Is Caused by Mutations in the Sodium-Phosphate Cotransporter Gene SLC34A3

Abstract: Hypophosphatemia due to isolated renal phosphate wasting results from a heterogeneous group of disorders. Hereditary hypophosphatemic rickets with hypercalciuria (HHRH) is an autosomal recessive form that is characterized by reduced renal phosphate reabsorption, hypophosphatemia, and rickets. It can be distinguished from other forms of hypophosphatemia by increased serum levels of 1,25-dihydroxyvitamin D resulting in hypercalciuria. Using SNP array genotyping, we mapped the disease locus in two consanguineous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
238
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(244 citation statements)
references
References 32 publications
2
238
1
3
Order By: Relevance
“…Recently, a genome-wide scan combined with homozygosity mapping has found a single nucleotide deletion in the Na/Pi-2c cotransporter gene in all affected individuals with HHRH (Bergwitz et al 2006, Lorenz-Depiereux et al 2006a. Interestingly, genomic deletion of Na/Pi-2c from mice has produced minor phenotypes (Segawa et al 2006) when compared with Na/Pi-2a-ablated mice, again suggesting that there might be differences in the regulation of phosphate homeostasis in humans and mice, and that the Na/Pi-2c cotransporter may have more important regulatory functions in maintaining phosphate homeostasis in humans.…”
Section: Renal Regulation Of Phosphate Homeostasismentioning
confidence: 99%
“…Recently, a genome-wide scan combined with homozygosity mapping has found a single nucleotide deletion in the Na/Pi-2c cotransporter gene in all affected individuals with HHRH (Bergwitz et al 2006, Lorenz-Depiereux et al 2006a. Interestingly, genomic deletion of Na/Pi-2c from mice has produced minor phenotypes (Segawa et al 2006) when compared with Na/Pi-2a-ablated mice, again suggesting that there might be differences in the regulation of phosphate homeostasis in humans and mice, and that the Na/Pi-2c cotransporter may have more important regulatory functions in maintaining phosphate homeostasis in humans.…”
Section: Renal Regulation Of Phosphate Homeostasismentioning
confidence: 99%
“…8,9 Two types of HR differ biochemically from the four described types, as they are characterised by hypercalciuria: Hereditary HR with hypercalciuria (HHRH; MIM 241530), where the hypercalciuria is due to increased serum 1,25(OH) 2 D. The inheritance is autosomal recessive and the disease is caused by a mutation in the sodium-cotransporter gene (SLC34A3; MIM 609826), identified in 2006. 10,11 The second type is X-linked recessive HR (MIM 300554), characterised by proximal renal tubulopathy and Fanconi syndrome caused by a mutation in the gene coding for the chloride channel 5 (CLCN5; MIM 300008). 12,13 Current recommendations on medical treatment of the HR types without hypercalciuria are intermittent oral phosphate supplementation in combination with alfacalcidol, carefully adjusted to avoid the development of secondary hyperparathyroidism or nephrocalcinosis.…”
Section: Introductionmentioning
confidence: 99%
“…Other types of mutations include silent and donor splice site mutations, and most of the mutations were associated with loss of function in SLC34A3 protein. 23 In the 21 kindred studies, 43% of described SLC34A3 mutations were homozygous while 38% and 19% consisted of compound heterozygous mutations and heterozygous mutations, respectively. 25 SLC34A1-3 encodes sodium-phosphate cotransporters type 2 (SLC34a1; Napi-2a/SLC34a2; Napi2b/SLC34a3; Napi-2c).…”
Section: Autosomal Dominant Hypophosphatemic Ricketsmentioning
confidence: 99%
“…However, familial studies revealed that single mutations could also cause some clinical symptoms of HHRH. 23,28 Bone pain, muscle weakness, and pseudofractures are common symptoms of HHRH. In comparison with other types of rickets, patients affected by HHRH exhibit an increase in serum 1,25(OH)2D.…”
Section: Autosomal Dominant Hypophosphatemic Ricketsmentioning
confidence: 99%
See 1 more Smart Citation